الشيخ نعيم النعيمي حياته وإسهاماته الفكرية والإصلاحية - بوطبة, لخضر (جامعة الوادي - University of Eloued, 2022)
على الرغم من الجهود المضنية التي بذلها الشيخ نعيم النعيمي، في حقل التعليم والإصلاح، ونشاطه المشهود له في جمعية العلماء المسلمين، إلا أنه لم يحظ بالتأريخ لشخصه، وبالدراسة والبحث من قبل الباحثين والكتاب، ولا تزال جوانب كثيرة من حياته يلفها الغموض، يرمي مقالنا هذا إلى تسليط الضوء على شخصية بارزة في تاريخ الجزائر المعاصر كان لها تأثير قوي في الحياة الفكرية والأدبية. Despite the strenuous efforts of Sheikh Naim Al-Nuaimi, in the field of education and reformation, and his proven activity within the Association of Muslim’s Ulamas, scholars and historical researchers have not paid enough attention to this person, where a large port of his life is still shrouded in mystery. So, I try in this article to shed on a prominent figure in the contemporary history of Algeria, who has had a strong influence on intellectual life and literature.
مقال
Keywords: نعيم النعيمي-الإصلاح- العالم-الأديب-الجزائر; Naim Al-Naimi-Reforme-Scientist-Writer-Algeria.